2017
DOI: 10.1371/journal.pone.0174320
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging of posterolateral plica of the elbow joint: Asymptomatic vs. symptomatic subjects

Abstract: BackgroundMagnetic resonance imaging (MRI) may be useful to diagnose a posterolateral plica syndrome of the elbow joint because this syndrome has less clear clinical features. The purposes of this study were to document mediolateral and sagittal dimensions of a posterolateral synovial fold and to determine the proportion of subjects with the posterolateral plica in asymptomatic elbows. We also aimed to determine whether the dimensions of the posterolateral synovial fold and the prevalence of the plica differ b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 10 publications
(31 reference statements)
0
21
0
Order By: Relevance
“…Choi et al found that symptomatic patients are more likely to have larger plicae on MRI, covering 30% of the radial head on either mediolateral or sagittal (or anteroposterior) dimension. 71 However, an earlier work by Ruiz de Luzuriaga et al did not reproduce the result to a statistical significance. 72 A cutoff thickness of 2.6 mm on MRI was also suggested to help identify patients with plica syndrome but was not shown to be statistically significant.…”
Section: Imaging the Posterolateral Plicamentioning
confidence: 84%
See 2 more Smart Citations
“…Choi et al found that symptomatic patients are more likely to have larger plicae on MRI, covering 30% of the radial head on either mediolateral or sagittal (or anteroposterior) dimension. 71 However, an earlier work by Ruiz de Luzuriaga et al did not reproduce the result to a statistical significance. 72 A cutoff thickness of 2.6 mm on MRI was also suggested to help identify patients with plica syndrome but was not shown to be statistically significant.…”
Section: Imaging the Posterolateral Plicamentioning
confidence: 84%
“…61 It can be visualized in 92 to 98% of elbows in healthy volunteers. 61,71 Sagittal and coronal planes are most useful to visualize the posterolateral plica using T2-weighted imaging (or other fluid-sensitive sequences such as proton-density fat-suppressed (PD FS) or spectral attenuated inversion recovery [SPAIR]). 61,71,72 However, the rate of MRI visualization of the radiohumeral plica is not consistently high across the literature, with Vahlensieck et al detecting only 24% in their 42 elbow cadaveric specimens.…”
Section: Imaging the Posterolateral Plicamentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, several studies demonstrate that RHSPS can often be associated with alterations of the radial head [1,2,4,6,14,17] and capitellum [1,2,6,7]. It is postulated that the mechanical abrasion by a snapping plica may produce chondromalacia along the radial head and capitellum [22], but it has not been clearly demonstrated whether there is a direct significant correlation between both of them.…”
Section: Pathophysiological Featuresmentioning
confidence: 99%
“…RHSPS may be confused with lateral epicondylitis [2, 3•, 4-6, 9, 13, 24], but it must also be included in the differential diagnosis of other clinical entities that present with anterolateral and/or posterolateral elbow pain [1, 4-8, 10, 12, 24], snapping [1, 2, 3•, 5, 9-11, 13], catching [1, 3•, 4, 13], mobility restriction [3•, 4, 6, 13, 18, 29], pitching [29], clicking [4][5][6], locking/blockage [4,11], popping [11,13] and/or swelling [6]. RHSPS can be an isolated condition or it can be associated with other elbow abnormalities [9,17,31].…”
Section: Clinical Manifestationsmentioning
confidence: 99%